KEMAMPUAN DEGRADASI DARI ISOLAT BAKTERI LIGNOLITIK ASAL CACING TANAH (Lumbricus rubellus) PADA SUBSTRAT GULMA TANAMAN PANGAN - J. Y. F., Marbun; Sutama, I N. S.; Mudita, I M.; Wijana, I W. (Jurnal Peternakan Tropika, 2016)
A research aiming to identify and evaluate lignin degradation capability of lignolytic bacteria isolate isolated from earthworms on weeds crops substrates have been done in Nutrition and Forage Laboratory of Animal Husbandary Faculty, Udayana University for 3 (three) months. Evaluation on the degradation capability of lignolytic substrate was based on clear zone diameter that was formed in the substrates of water hyacinth, and water lettuce leaves. The research was based on Completely Randomized Design (CRD) with 3 (three) treatments and 3 (three) repetitions. The treatments are lignolytic bacteria isolates with codes EB1LG, EB2LG and EB3LG. Research result showed that on the water hyacinth and water lettuce leave substrates, showed that bacteria isolate coded EB1LG has highest clear zone diameters (1,525 cm and 1,528 cm) were 1,05% and 0,64% or 0,15% and 1,32% higher than bacteria isolates coded EB2LG and EB3LG, yet statistically it was not significantly different (P>0.05). Based on the research it can be concluded that on all substrates, namely water hyacinth, and water lettuce leaves, the three lignolytic bacteria isolated from earthworms have almost identical capability in degrading lignin.
Keywords: earthworms, substrate degradation, lignolytic bactery isolate